The Effects of Length of Residence and Exposure to Violence on Perceptions of Neighborhood Safety in an Urban Sample. - Guo, Monica; O'Connor Duffany, Kathleen; Shebl, Fatma M; Santilli, Alycia; Keene, Danya E (Journal of Urban Health, 2018)
Perceptions of neighborhood safety shape the well-being of individuals and communities, affecting neighborhood walkability, associated physical activity behaviors, and health conditions. However, less is known about the factors that determine perceptions of safety. One factor that may affect perceptions of neighborhood safety is the length of time someone has lived in their neighborhood. We use a representative, adult sample of urban low-income residents from the 2015 New Haven Health Survey (n = 1189) to investigate the associations between length of residence (new residents of < 1 year in neighborhood versus longer-term residents of 1 or more years in neighborhood) and perceptions of neighborhood safety (whether feeling unsafe to walk at night). We then examine the potential moderating effect of exposure to neighborhood violence on these associations. We find that the association between length of residence and perceived safety differs by exposure to neighborhood violence. Among those unexposed to neighborhood violence, longer-term neighborhood residents were more likely to feel unsafe compared to new residents (OR = 2.03, 95% CI 1.19, 3.45). Additionally, the effect of exposure to violence on feelings of safety was larger for new residents (OR = 9.10, 95% CI 2.72, 30.44) compared to longer-term residents (OR = 1.88, 95% CI 1.28, 2.77). Our findings suggest that length of residence may have implications for feelings of safety, and that experiences of violence may uniquely contribute to feelings of unsafety among new residents. These findings hold implications for interventions and policy efforts aimed at neighborhood safety improvements through community development, housing, or city urban planning initiatives, particularly for new neighborhood residents or those who experience neighborhood violence.
11 citations (Crossref) [2023-10-31] Place: United States Guo, Monica. Yale School of Public Health, New Haven, CT, USA. monica.guo@yale.edu. O'Connor Duffany, Kathleen. Yale School of Public Health, New Haven, CT, USA. O'Connor Duffany, Kathleen. Community Alliance for Research and Engagement, New Haven, CT, USA. Shebl, Fatma M. Yale School of Public Health, New Haven, CT, USA. Shebl, Fatma M. Community Alliance for Research and Engagement, New Haven, CT, USA. Santilli, Alycia. Community Alliance for Research and Engagement, New Haven, CT, USA. Santilli, Alycia. Southern Connecticut State University, New Haven, CT, USA. Keene, Danya E. Yale School of Public Health, New Haven, CT, USA.
Keywords: *Exposure to Violence/px [Psychology]; *Exposure to Violence/sn [Statistics & Numerical Data]; *Poverty/px [Psychology]; *Poverty/sn [Statistics & Numerical Data]; *Residence Characteristics/sn [Statistics & Numerical Data]; *Safety/sn [Statistics & Numerical Data]; *Urban Population/sn [Statistics & Numerical Data]; Adult; Age Factors; Aged; Exposure to Violence; Exposure to violence; Female; Humans; Length of residence; Male; Middle Aged; Neighborhood; Perceptions of safety; Poverty; Residence Characteristics; Residential stability; Safety; Urban Population; Violence; Young Adult; adult; age; aged; demography; dept.pch; exposure to violence; female; human; male; middle aged; peer-reviewed; poverty; psychology; safety; urban population; young adult

Intersectional experiences of discrimination in a low-resource urban community: An exploratory latent class analysis - Earnshaw, Valerie A.; Rosenthal, Lisa; Gilstad-Hayden, Kathryn; Carroll-Scott, Amy; Kershaw, Trace S.; Santilli, Alycia; Ickovics, Jeannette R. (Journal of Community and Applied Social Psychology, 2018)
There have been increasing calls for the application of an intersectionality framework to understand and address discrimination and health inequities among diverse communities. Yet there have been theoretical debates regarding to whom intersectionality applies and how intersectional experiences of discrimination are associated with health outcomes. The current study aimed to contribute to these theoretical debates and inform practical applications to reduce health inequities. Data were drawn from a community health survey in New Haven, CT (N=1,293 adults) and analysed using latent class analysis. Results yielded 4 classes. Members of the 4 classes were similar sociodemographically. Three classes of participants reported experiencing discrimination, and members of these classes had greater stress, higher rates of smoking and sleep disruption, and worse overall health than members of the class reporting no discrimination. Members of 2 classes made multiple, or intersectional, attributions for discrimination, and members of these classes reported the most frequent discrimination. Findings suggest that community members who are sociodemographically similar may have diverse discrimination experiences. Multilevel interventions that address multiple forms of discrimination (e.g., racism and sexism) may hold promise for reducing discrimination and, ultimately, health inequities within low-resource urban community settings.
17 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/032-249-301-742-222 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: adult; article; dept.pch; discrimination; female; health inequities; human; human experiment; intersectionality; latent class analysis; major clinical study; male; peer-reviewed; public health; racism; sexism; sleep; smoking; stress; theoretical study; urban population